2000
DOI: 10.1111/j.0014-3820.2000.tb00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation by Distance in Equilibrium and Nonequilibrium Populations of Four Talitrid Species in the Mediterranean Sea

Abstract: Allozymic variation at 21-23 loci was studied in 28 populations of Talitrus saltator, 23 populations of Orchestia montagui, 13 populations of O. stephenseni, and five populations of Platorchestia platensis from the Mediterranean Basin. Different levels of gene flow (Nmtheta) were detected within each species at the scale of the whole Mediterranean: O. montagui and P. platensis had low population structure, with levels of Nmtheta > or = 1, whereas the T. saltator and 0. stephenseni populations have values of Nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…More generally, previous allozyme-based studies on O. montagui revealed high or very high levels of gene flow at the scale of the Mediterranean Sea (De Matthaeis et al 2000a). Although our sampling was currently limited to a relatively low number of locations, it is worth noting that, whatever geographic scale is considered, we almost invariably retrieved a significant divergence among sampled populations.…”
Section: Population Genetic Structurementioning
confidence: 77%
See 3 more Smart Citations
“…More generally, previous allozyme-based studies on O. montagui revealed high or very high levels of gene flow at the scale of the Mediterranean Sea (De Matthaeis et al 2000a). Although our sampling was currently limited to a relatively low number of locations, it is worth noting that, whatever geographic scale is considered, we almost invariably retrieved a significant divergence among sampled populations.…”
Section: Population Genetic Structurementioning
confidence: 77%
“…The vast majority of them is based on allozymes (Angelini et al 1996;Cervelli et al 2006;De Matthaeis et al 1995, 2000a Here we present the first study that applies simultaneously mitochondrial and nuclear markers in a talitrids species in order to describe its population structure. Our study acts as a preliminary and exploratory research, seeking to address the interplay between population genetic structure and abiotic forces in the talitrid species O. montagui, by using markers with different evolutionary properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous studies based on allozymes have revealed a poor genetic structure of O. montagui populations (De Matthaeis et al 1995, 2000a, 2000bAngelini et al 1996;Cervelli et al 2006). More recent studies that were based on more variable and informative markers (cytochrome oxidase subunit I and microsatellites) showed signatures of local differentiation (Pavesi et al 2012(Pavesi et al , 2013 and differed from previous hypotheses.…”
Section: Introductionmentioning
confidence: 95%